2020
DOI: 10.1016/j.icarus.2020.113899
|View full text |Cite
|
Sign up to set email alerts
|

Present-day gully activity in Sisyphi Cavi, Mars – Flow-like features and block movements

Abstract: The continuously increasing number of multi-temporal high-resolution images from the surface of Mars offers the possibility for detailed studies of present-day surface activity. In this study we investigated all gullies in the Sisyphi Cavi region (355° E, 71° S) of the south polar region of Mars. This region is influenced by the seasonal deposition of a decimeters-thick translucent slab ice in late autumn/winter and its subsequent sublimation in spring. We mapped all gullies (n = 17.760) and measured their ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 80 publications
(141 reference statements)
2
13
0
Order By: Relevance
“…In impact craters, such alcoves normally expand as theater-shape depressions within the wall or rim of the structure or mid-slope within the hill slope, on which they have formed (Malin & Edgett, 2000;Kumar et al, 2010;De Haas et al, 2015;Conway et al, 2018). On Moon and Mars, such alcoves show a wide range of morphologies and develop in a broad range of settings ranging from the walls and central peaks of impact structures to valley walls, hills, dunes and polar pits (Malin & Edgett, 2000;Sharpton, 2014;Harrison et al, 2015;Conway et al, 2018;Raack et al, 2020). On Mars, alcoves are considered excellent sites for exploration for evidence of life (De Hon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In impact craters, such alcoves normally expand as theater-shape depressions within the wall or rim of the structure or mid-slope within the hill slope, on which they have formed (Malin & Edgett, 2000;Kumar et al, 2010;De Haas et al, 2015;Conway et al, 2018). On Moon and Mars, such alcoves show a wide range of morphologies and develop in a broad range of settings ranging from the walls and central peaks of impact structures to valley walls, hills, dunes and polar pits (Malin & Edgett, 2000;Sharpton, 2014;Harrison et al, 2015;Conway et al, 2018;Raack et al, 2020). On Mars, alcoves are considered excellent sites for exploration for evidence of life (De Hon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Monitor the spring and summertime retreating polar caps for signs of sediment flows and possibly even geysers caused by subliming CO 2 ice. This type of activity has already been suggested to cause substantial changes mid-latitude gullies [23] and on dunefields [24]. k.) Address questions of spatial extent (locality and 'deep transport') of Martian cloud structure, which is anticipated to be on the order of 1km width and is crucial to understanding differences between terrestrial and Martian mesospheric dynamics [25].…”
Section: Martian Example Case Study Lidar -Aspenmentioning
confidence: 96%
“…(2010) showed that gully activity was seasonal, favoring cold seasons. Subsequent work (Dundas, Diniega, & McEwen, 2015; Dundas et al., 2012; Dundas, McEwen, et al., 2019; Raack et al., 2015, 2020; Vincendon, 2015) ultimately showed a strong temporal correlation with the presence of seasonal CO 2 frost, indicating that most present‐day flows are driven by this frost. Northern hemisphere gullies are less active than those in the south, in addition to being less common, and the flows so far observed in the north have small geomorphic effects in most cases.…”
Section: Mass Wasting and Slope Processesmentioning
confidence: 98%